Human neutrophil peptide‐1 inhibits thrombus formation under arterial flow via its terminal free cysteine thiols. (13th March 2019) - McDaniel, Jenny K.; Abdelgawwad, Mohammad S.; Hargett, Audra; Renfrow, Matthew B.; Bdeir, Khalil; Cao, Wenjing; Cines, Douglas B.; Zheng, X. Long
Abstract : Essentials Biological activity of human neutrophil peptide (HNP)‐1 in hemostasis under physiological conditions is not fully understood. HNP‐1 inhibits the adhesion/aggregation of murine platelets on a fibrillar collagen surface or an activated endothelial cell surface under flow. The anti‐adhesion activity appears to depend on the terminal free thiols of HNP‐1, which may inhibit VWF‐VWF lateral associations. Our results suggest a protective role and potential novel therapeutic use of HNP‐1 for arterial thrombosis. Summary: Background: Human neutrophil peptides (HNPs), also known as α‐defensins, are released from degranulated neutrophils and play an important role in innate immunity. However, their biological roles in hemostasis under flow are not fully explored. Objective: This study aims to determine the role of HNP‐1 on platelet adhesion and aggregation on a collagen surface or ultra large von Willebrand factor (ULVWF) on endothelium under flow and elucidate the structural elements required for its activity. Methods: Anticoagulated whole blood from wild‐type or Adamts13 −/− mice was incubated with a fluorescein‐conjugated anti‐human CD41 in the presence of increasing concentrations of a synthetic HNP‐1 and perfused over a collagen surface or a tumor necrosis factor (TNF)‐α activated murine endothelial cell surface under arterial flow. The rate of accumulation and the final surface coverage of fluoresceinated murine platelets or the rate of forming platelet‐decorated ULVWF strings were determined using the BioFlux microfluidic system. Results: HNP‐1 inhibited the rate and final coverage of fluorescein‐labeled murine platelets on a fibrillar collagen surface under flow (100 dyne/cm 2 ) in a concentration‐dependent manner and the anti‐adhesive activity of HNP‐1 depended on its terminal free cysteine thiols. HNP‐1 (20 μM) also dramatically inhibited the formation of platelets‐decorated ULVWF strings on TNF‐α activated murine endothelial surface under arterial flow. Conclusions: Our results demonstrate for the first time an antiplatelet adhesion or antithrombotic activity of HNP‐1; this activity depends on its terminal free thiols, likely affecting VWF‐VWF lateral associations. These findings may suggest a potential novel therapeutic strategy for arterial thrombosis.